PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT KEMAS INDAH MAJU - Nur 'Aini, Najmah; Keisyarani Arifin, Qoria; Rosalina, Sinta (Faculty of economcs Universitas Singaperbangsa Karawang, 2022)
Carrying out duties and obligations certainly creates some pressure on each individual. Of course, this pressure can be overcome or minimized in various ways, one of which is motivation. Within the company. Leaders play a role in encouraging their subordinates to be able to carry out their duties and obligations properly. With motivation from superiors, subordinates feel supported and pressure is gradually reduced. Motivation from superiors is certainly needed by every individual, including employees of Kemas Indah Maju Company where the majority of employees have pressure or stress levels at work. Therefore, this research focuses on studying the effect of motivation on employee performance. The method used in this research is the quantitative method. The sources taken in this study amounted to 5 informants with details of 3 permanent employees and 2 contract employees at Kemas Indah Maju Company. The result is that motivation greatly influences the performance of employees in carrying out their duties. Employees who receive motivation tend to try to provide the best results for the company.